Books and potential parasitic contamination in a university library in the north of Espírito Santo - Passinato, Arthur Oliveira; Souza, Marco Antônio Andrade de (Brazilian Journal of Production Engineering, 2024)
Enteroparasitosis is a serious public health problem worldwide. In Brazil, despite the relevance and topicality of the problem, few studies have carried out parasitological analyzes on surfaces. This study sought to carry out parasitological evaluations on books in the university library at Ceunes/UFES, São Mateus-ES. The method proposed by Graham, with modifications, popularly known as the tape method or duct tape method, which consists of affixing adhesive tape to tactile aids, was used to carry out the analysis. During the period from September 2022 to August 2023, 100 books were analyzed. Of a total of 300 samples obtained for analysis, 17 (5.67%) tested positive: 6 (35.29%) for Entamoeba coli, 5 (29.41%) for Ascaris lumbricoides, 2 (11.76%) for Taenia sp., 2 (11.76%) for Hymenolepis nana, and 2 (11.76%) for Ancylostoma sp. Considering that enteroparasitoses are intestinal infections transmitted through the ingestion of water, food, or contaminated hands, the results of this study alert us to the need to improve individual hygiene processes, given the significant finding of parasitic forms in textbooks widely used by students.
Keywords: Saúde Pública; Parasitologia; Livros; Universidade; Graham